Expression of type III collagen in hypertrophic gingival tissue of patients with orthodontic treatment: a pilot study - Víctor Hugo Simancas-Escorcia (Universidad de Antioquia, 2020)
Introduction: gingival hypertrophy (GH) is the uncontrolled increase in gingival volume induced by different etiological factors, including orthodontic treatment. This pathology is characterized by changes in epithelial and connective tissue, including modifications in the extracellular matrix. The present study determined the presence and distribution of type III collagen in tissues of patients with GH wearing fixed orthodontic appliances. Methods: 12 samples of gingival tissue were obtained from patients undergoing periodontal surgery. They were divided into two groups, the first with healthy patients (control; n = 6) and the second with patients diagnosed with GH and orthodontic treatment (patients; n = 6). Each obtained sample was subjected to the hematoxylin-eosin stain, Masson-Goldner staining, and type III collagen immunohistochemistry. Results: the hematoxylin-eosin and Masson-Goldner histological stains showed hypertrophia of epithelial tissue and connective tissue with a marked collagen fiber increase in the gingival tissue of orthodontic wearers with GH compared to individuals in the control group. The gingival tissue of patients with GH caused by orthodontic treatment showed a distribution and location of type III collagen near the basal lamina, around the blood vessels, but unlike the control group, its location was noticeable throughout the connective tissue. Conclusion: the gingival tissues of orthodontic wearers with GH experience an increase in the number and density of collagen fibers. Type III collagen seems to lose its usual location in the gingival tissues of orthodontic wearers with GH.